Extended TOPSIS method for multi-criteria group decision-making problems under cubic intuitionistic fuzzy environment - Garg, H; Kaur, G (Scientia Iranica. Transaction E, Industrial engineering, 2020)
The objective of this work is to present a novel Multi-Criteria Group DecisionMaking (MCGDM) method under the Cubic Intuitionistic Fuzzy (CIF) environment by integrating it with the extended TOPSIS method. In the existing studies, uncertainties, which are present in the data, are handled with either Interval-Valued Intuitionistic Fuzzy Sets (IVIFS) or Intuitionistic Fuzzy Set (IFS) information, which may lose some useful information of alternatives. On the other hand, CIF Set (CIFS) handles the uncertainties by considering both the IVIFS and IFS simultaneously. Thus, motivated by this, in the present work, some series of distance measures between the pairs of CIFSs were presented, and their various relationships were investigated. Further, under this environment, a group decision-making method based on the proposed measure was presented by considering the different priority pairs of the decision-makers. A practical example was provided to verify the developed approach and, demonstrate its practicality and feasibility, their results were compared with those of the several existing approaches.